Teacher target language input and young learners’ aural comprehension of English - Erk Mirna; Takač Višnja Pavičić (ExELL (Explorations in English Language and Linguistics))
The quantity of target language input available to learners contributes to the understanding of target language development. The present paper reports on a longitudinal study of the relationship between the amount of non-native teachers’ EFL input and learners’ aural achievement in instructed SLA. Young learners (N=132) were followed over a three-year period. High variability in teacher use of EFL was found. Results of correlational analyses and group comparisons pointed to a longitudinal advantage of participants exposed to instruction dominated by teacher target language use during their first two years of formal EFL learning. Directions for future research on the use of different languages and their relation to learners’ achievement are discussed in the context of early formal foreign language study.